Analisis Laporan Keuangan dalam Menilai Kinerja Keuangan pada PT. Tempo Scan Pacific TBK - Pipih Ridayanti; Sihabudin; Robby Fauji (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The financial overall performance of an organisation is an outline of the sports that have been achieved to acquire commercial enterprise goals at a selected time. It also serves as a reference cloth for finding out the extent to which the organisation has achieved its fulfilment goals so that it will preserve its balance. you can examine the financial reports of the enterprise to learn about its monetary overall performance. A dating analysis of the objects within the economic reviews, also known as financial report evaluation, is important for the reviews to be meaningful for fascinated events. utilising liquidity ratios (contemporary ratio, brief ratio, and cash ratio) and profitability ratios (net income margin, gross profit margin, return on belongings, and return on equity), the reason of this look at is to observe PT Tempo Scan Pacific Tbk's financial performance from 2019 to 2023. the general liquidity ratio indicates that the agency is in precise health, regardless of fluctuations between 2019 and 2023. The decline within the profitability ratio indicates that the commercial enterprise is in negative condition.